Using a tripod as a chiral chelating ligand: chemical exchange between equivalent molecular structures in palladium catalysis with 1,1,1-tris(oxazolinyl)ethane (“Trisox”)$ddedicated to Professor Peter Hofmann on the occasion of his 60th birthday - Foltz-César, Carole; Enders, Markus; Bellemin, Stéphane; Wadepohl, Hubert; Gade, Lutz H. (Chemistry - a European journal, 2007)
Threefold symmetrical chiral podands may simplify the stereochemistry of key catalytic intermediates for cases in which they only act as bidentate ligands. This applies to systems in which chemical exchange between the different κ2-coordinated forms takes place and in which the non-coordinated sidearm may play a direct or indirect role at some earlier or later stage in the catalytic cycle. Palladium(II)-catalysed allylic substitutions provide appropriate test reactions along these lines. A series of neutral dichloropalladium(II) complexes, [PdCl2(iPr-trisox)] (1 a), [PdCl2(Ph-trisox)] (1 b), [PdCl2(Bn-trisox)] (1 c) and [PdCl2(Ind-trisox)] (1 d) (trisox=1,1,1-tris(oxazolinyl)ethane) were synthesised by reaction of the respective trisox derivative with [PdCl2(PhCN)2] and characterised inter alia by 15N NMR spectroscopy. Direct detection of the heteronuclei without isotope enrichment and with “normal” sample concentrations was achieved with the aid of a cryogenically cooled NMR probe on a 600 MHz NMR spectrometer. Whereas the 15N nuclei of the coordinated oxazoline rings resonate at δ=160-167 ppm and appear as two singlets due to their diastereotopicity, the signal assigned to the dangling oxazoline “arm” is observed at δ=238-240 ppm. Variable-temperature NMR studies along with a systematic series of magnetisation transfer experiments established exchange between ligating and non-ligating oxazoline rings. Reaction of [Pd(allyl)(cod)]BF4 (cod=cyclooctadiene) with Ph-trisox in CH2Cl2 gave the corresponding allyl complex 2, for which fast exchange between the three oxazoline heterocycles as well as between the exo and endo diastereomers was observed along with a very slow η3-η1-η3 process of the allyl fragment (magnetisation transfer). Palladium(0) complexes were prepared by reaction of trisox derivatives or sidearm-functionalised BOX (BOX=bis(oxazolinyl)dimethylmethane) ligands with [Pd(nbd)(alkene)] (nbd=norbornadiene, alkene=maleic anhydride or tetracyanoethylene). X-ray diffraction studies of the iPr-trisox and Ph-trisox complexes (3 a and 3 b) established Y-shaped trigonal planar coordination geometries with the trisox ligand coordinated in a bidentate fashion, whilst the π-coordinated maleic anhydride ligand adopts one of the two possible diastereotopic orientations. As the catalytic test reaction, the allylic alkylation of 1,3-diphenylprop-2-enyl acetate substrate with dimethyl malonate as nucleophile (in the presence of N,O-bis(trimethylsilyl)acetamide) was investigated for the trisox derivatives, their BOX analogues, and a series of less symmetric “sidearm” functionalised bisoxazolines. The trisoxazoline-based catalysts generally induce a better enantioselectivity compared to their bisoxazoline analogues and display significant reduction of the induction period as well as rate enhancement.
First published: 04 July 2007
Gesehen am 18.11.2022
Keywords: Festschrift